A new species of Aphanoblastella (Monogenea: Dactylogyridae) parasitic on Rhamdia quelen (Siluriformes: Heptapteridae) from Southeastern Brazil - DOI: 10.4025/actascibiolsci.v31i3.4917 - Carvalho, Adriano Reder de; Tavares, Luiz Eduardo Roland; Luque, José Luis (Acta Scientiarum. Biological Sciences, 2009)
Aphanoblastella juizforense sp. nov. is described in the gills of the heptapterid fish Rhamdia quelen (Quoy et Gaimard, 1824) from the Paraibuna River, Juiz de Fora, Minas Gerais State, Brazil. The new species can be separated from all congeners by the long coiled copulatory organ with one counterclockwise ring; sinuous accessory piece and for the robust shape of the ventral bar.